How Does It Feel To Be at University? Affect in Contemporary North American Campus Fiction - Ferens, Dominika (2024)
This paper explores the role of affect in academic life, using as case studies three North American campus novels narrated from undergraduate and graduate students’ perspectives. While the case studies – Sarah Henstra’s The Red Word (2018), Brandon Taylor’s Real Life (2020), and Juliet Lapidos’s Talent (2019) – include humorous elements, they tend to foreground the student-protagonists’ emotional responses to their precarious position in the competitive and hierarchical world of academia. In each novel, the emotional impact of academic life is additionally complicated by the students’ gender, class, race, and/or sexuality. Arguably, out of the many affects young people experience every day, two play a special role in academia: interest and shame. Referring to the affect theories of Silvan S. Tomkins (2008), Paul J. Silvia (2005, 2008), Pierre Bourdieu ([1994] 1998), and Ann Cvetkovich (2012), this paper attempts to show how writers tell emotionally charged stories about campus life, structured by the interplay of interest and shame.
Keywords: campus fiction; academia; student; affect; interest; shame; resistance